2019
DOI: 10.1002/jnm.2589
|View full text |Cite
|
Sign up to set email alerts
|

An improved open‐short equivalent circuit model for CMOS transistors de‐embedding

Abstract: In this paper, the open and short de-embedding structures are studied. The parallel terminal coupling effect, the loss of vias, and the interconnects are considered. On this basis, the above parasitic effects are characterized by the equivalent circuit model. To validate the model, open and short test structures are manufactured and measured. By comparing the measurement data with the modeling data, the proposed model achieves high accuracy. The rootmean-square error of scattering parameter is less than 0.0145… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Bashir et al presented a scalable small‐signal model for RF CMOS transistors. Besides compact models, progress of artificial neural network‐based modeling for small‐signal models is presented by Marinković et al Accurate de‐embedding for CMOS transistors reported by Wang et al and Xie and Xu can be found helpful for active device modeling. Different from semiconductor devices, electric vacuum devices have high‐power, high‐efficiency, and high‐gain characteristics in the millimeter‐wave and THz frequency bands.…”
mentioning
confidence: 99%
“…Bashir et al presented a scalable small‐signal model for RF CMOS transistors. Besides compact models, progress of artificial neural network‐based modeling for small‐signal models is presented by Marinković et al Accurate de‐embedding for CMOS transistors reported by Wang et al and Xie and Xu can be found helpful for active device modeling. Different from semiconductor devices, electric vacuum devices have high‐power, high‐efficiency, and high‐gain characteristics in the millimeter‐wave and THz frequency bands.…”
mentioning
confidence: 99%